End-stage ADPKD with a low-frequency PKD1 mosaic variant accelerated by chemoradiotherapy - Hiroaki Hanafusa; Hiroshi Yamaguchi; Naoya Morisada; Ming Juan YE; Riki Matsumoto; Hiroaki Nagase; Kandai Nozu (Human Genome Variation)
Abstract Autosomal dominant polycystic kidney disease (ADPKD) is commonly caused by PKD1, and mosaic PKD1 variants result in milder phenotypes. We present the case of a 32 year-old male with chronic active Epstein–Barr virus who underwent bone marrow transplantation with chemoradiotherapy at age 9. Despite a low-frequency mosaic splicing PKD1 variant, he developed severe renal cysts and end-stage renal disease in his 30 s. This case highlights how environmental factors may contribute to the genetic predisposition to ADPKD.